2017
DOI: 10.3727/105221616x693891
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR-23, miR-27, and miR-24 Alters Fetal Liver Development and Blocks Fibrosis in Mice

Abstract: MicroRNAs (miRNAs) regulate cell fate selection and cellular differentiation. miRNAs of the miR23b polycistron (miR-23b, miR-27b, and miR-24) target components of the TGF-β signaling pathway and affect murine bile ductular and hepatocyte cell fate selection in vitro. Here we show that miR-23b polycistron miRNAs directly target murine Smad4, which is required for TGF-β signaling. Injection of antagomirs against these miRNAs directly into E16.5 murine fetuses caused increased cytokeratin expression in sinusoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…MiR-24 is also a member of miR-23b cluster that could be used as non-invasive biomarkers in fibrogenic liver diseases (Oksuzet al, 2015). Although some other studies on miR-23b cluster regulating HSC activation are inconsistent with our study (Yuan et al, 2011;Zeng et al, 2016;Hall et al, 2017;Rogler et al, 2017), a quite recent study showed that knockdown of miR-23, miR-27, and miR-24 had a distinctly blocking effect on mouse liver fibrosis (Rogler et al, 2017), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…MiR-24 is also a member of miR-23b cluster that could be used as non-invasive biomarkers in fibrogenic liver diseases (Oksuzet al, 2015). Although some other studies on miR-23b cluster regulating HSC activation are inconsistent with our study (Yuan et al, 2011;Zeng et al, 2016;Hall et al, 2017;Rogler et al, 2017), a quite recent study showed that knockdown of miR-23, miR-27, and miR-24 had a distinctly blocking effect on mouse liver fibrosis (Rogler et al, 2017), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…We identified several highly abundant and specific miRNAs derived from hAFSC-exo, including let-7-5p, miR-22-3p, miR-27a-3p, miR-21-5p, and miR-23a-3p, all of which directly target TGF-βRs. Let-7-5p ( Elliot et al, 2019 ), miR-22-3p ( Hong et al, 2016 ), miR-27a-3p ( Zhang et al, 2019 ), and miR-23a-3p ( Rogler et al, 2017 ) have been previously shown to inhibit fibrotic diseases. Many studies have shown that these four miRNAs directly target the TGF-βR, and consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NADPH oxidases (NOXs) induces HSCs activation ( Jiang et al, 2010 ), and inhibition of NOX1/NOX4 has been shown to suppress fibrogenesis in the bile duct ligation (BDL) and CCl 4 models ( Aoyama et al, 2012 ; Crosas-Molist and Fabregat, 2015 ). The immune response, that has multiple interactions with the fibrogenic process, may be also a candidate for therapy ( Pellicoro et al, 2014 ); thus, several strategies to block the TGF-β activity have shown efficacy ( Vogt et al, 2011 ; Rogler et al, 2017 ), and inhibition of chemokines and their receptors demonstrated antifibrotic effects in rodent models of liver fibrosis ( Zaldivar et al, 2010 ; Seifert et al, 2015 ; Zubiete-Franco et al, 2017 ).…”
Section: Mechanisms Involved In the Pathogenesis Of Liver Fibrosismentioning
confidence: 99%